PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KONTRAK PADA MAHKAMAH KONSTITUSI REPUBLIK INDONESIA JAKARTA PUSAT - Puji, Puji Astuti; Laura Komala (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this study was to determine the influence of work discipline and work environment on the performance of contract employees at the Constitutional Court of the Republic of Indonesia, Central Jakarta, partially and simultaneously. The method used was quantitative. The sampling technique used the Slovin formula, and after calculations, a sample of 78 respondents was obtained. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination, and hypothesis testing. The results of this study are that work discipline has a significant effect on the performance of contract employees with the regression equation Y = 17.006 + 0.579X1, the correlation coefficient value is 0.677 (strong), the determination coefficient is 45.8% and the hypothesis test obtained t count > t table, namely (8.009 > 1.982). The work environment has a significant effect on the performance of contract employees with the regression equation Y = 14.408 + 0.644X2, the correlation coefficient value is 0.665 (strong), the determination coefficient is 44.2% and the hypothesis test obtained t count > t table, namely (7.765 > 1.982). Work discipline and work environment simultaneously have a significant effect on the performance of contract employees with the regression equation Y = 6.157 + 0.420X1 + 0.456X2. The correlation coefficient is 0.803 (strong), with a determination coefficient of 64.5%, while the remaining 35.5% is influenced by other variables. The hypothesis test yielded a calculated F value > F table value, namely (68.122 > 3.120). Keywords: Work Discipline, Work Environment, Contract Employee Performance